Perancangan UI/UX Point of Sale Berbasis Website Menggunakan Metode Design Thinking - Ananta, Falih; Taufik Ridwan; Nono Heryana (STMIK Budi Darma, 2024)
In facing increasingly intensive business dynamics, especially in the era of technological advances, Cafe Naluri has taken a progressive initiative by implementing a cashier application system as a strategic step to simplify and increase efficiency in recording financial transactions. Although point of sales applications have become an integral part of their operations, the existence of several obstacles, especially potential slowdowns in the transaction process, is a major concern that may impact customer satisfaction levels. In this context, this research aims to redesign the UI/UX design of the point of sales application, with the main focus on increasing operational efficiency and increasing customer satisfaction at Cafe Naluri. The design thinking method is the main approach, including the stages of empathy, definition, ideation, prototyping and testing, to ensure the resulting solution meets the actual needs of users. This process will be supported by data collection methods, such as observation and interviews, to gain a deeper understanding of user needs and expectations, as well as to identify potential improvements that can be implemented. It is hoped that this redesign will not only address existing weaknesses in the system, but will also simplify all actions carried out in Cafe Naluri's internal processes, including transactional aspects. The updated user interface will be carefully designed to ensure optimal usability, focusing on an intuitive and efficient user experience. Thus, it is hoped that the results of this redesign will have a positive impact in increasing operational efficiency and customer satisfaction levels